2013
DOI: 10.1007/s00253-013-4909-7
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic mining of feruloyl esterases from termite enteric flora

Abstract: A metagenome expression library was created from Trinervitermes trinervoides termite hindgut symbionts and subsequently screened for feruloyl esterase (FAE) activities, resulting in seven recombinant fosmids conferring feruloyl esterase phenotypes. The amino acid sequence lengths of the seven FAE encoding open reading frames (ORFs) ranged from 260 to 274 aa and encoded polypeptides of between 28.9 and 31.4 kDa. The highest sequence identity scores for the seven ORFs against the GenBank database were between 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…As different parts of the gut have different functions, their corresponding microbial structures and functions will change as well, which has been proven in the human body, chicken, mice and insects (Rashamuse et al., ; Rehman, Vahjen, Awad & Zentek, ; Stachler & Bibby, ; Warnecke et al., ). In this study, the metagenomic sequencing technology was used to analyze the diversity of bacterial community in the gut in different parts of the gut of sea cucumber ( A. japonicus ) and predict the biological functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As different parts of the gut have different functions, their corresponding microbial structures and functions will change as well, which has been proven in the human body, chicken, mice and insects (Rashamuse et al., ; Rehman, Vahjen, Awad & Zentek, ; Stachler & Bibby, ; Warnecke et al., ). In this study, the metagenomic sequencing technology was used to analyze the diversity of bacterial community in the gut in different parts of the gut of sea cucumber ( A. japonicus ) and predict the biological functions.…”
Section: Discussionmentioning
confidence: 99%
“…to study the abundance and diversity of the bacterial community in the gut (Table 4). The results indicated that the abundance and diversity of bacterial community in the gut during the earlier regeneration stage were on a rising trend, reached a peak during the 15th As different parts of the gut have different functions, their corresponding microbial structures and functions will change as well, which has been proven in the human body, chicken, mice and insects (Rashamuse et al, 2014;Rehman, Vahjen, Awad & Zentek, 2007;Stachler & Bibby, 2014;Warnecke et al, 2007). In this study, the metagenomic sequencing technology was used to analyze the diversity of bacterial community in the gut in different parts of the gut of sea cucumber (A. japonicus) and predict the biological functions.…”
Section: Metagenomic Analysismentioning
confidence: 92%
“…EstG34 had a specific activity of 10.3 U mg -1 , 0.65 U mg -1 and 0.11 U mg -1 on these substrates, respectively (Supplementary Figure S4). While there are relatively few characterised feruloyl esterases in the literature [43,44,45] EstG34 activity is comparable to two characterised fungal feruloyl esterases [46].…”
Section: Resultsmentioning
confidence: 77%
“…N. aquilinus feeds exclusively on wood, whereas C. fulviceps consumes more nitrogen rich organic matter, including either living or decaying plant tissues 84,85 . This difference in diet may explain the metabolic pathway profiles of each termite colony.…”
Section: Discussionmentioning
confidence: 99%